2013
DOI: 10.1093/nar/gkt374
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer networks revealed by correlated DNAse hypersensitivity states of enhancers

Abstract: Mammalian gene expression is often regulated by distal enhancers. However, little is known about higher order functional organization of enhancers. Using ∼100 K P300-bound regions as candidate enhancers, we investigated their correlated activity across 72 cell types based on DNAse hypersensitivity. We found widespread correlated activity between enhancers, which decreases with increasing inter-enhancer genomic distance. We found that correlated enhancers tend to share common transcription factor (TF) binding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…We asked whether co-accessible sites are closer together in the nucleus than unlinked sites at similar distances in the linear genome. Previous analyses of ENCODE cell lines reported that distal DHSs and promoters that display a correlation in their sensitivity to DNase I were closer in the nucleus according to chromosome conformation capture data than uncorrelated pairs of sites (Malin et al, 2013;Thurman et al, 2012). To test this in Cicero-based links, we used our updated sci-ATAC-seq protocol to generate chromatin profiles from 662 human lymphoblastoid cells (GM12878), for which high-resolution Hi-C data was recently generated (Rao et al, 2014).…”
Section: Co-accessible Dna Elements Exhibit Physical Proximitymentioning
confidence: 99%
“…We asked whether co-accessible sites are closer together in the nucleus than unlinked sites at similar distances in the linear genome. Previous analyses of ENCODE cell lines reported that distal DHSs and promoters that display a correlation in their sensitivity to DNase I were closer in the nucleus according to chromosome conformation capture data than uncorrelated pairs of sites (Malin et al, 2013;Thurman et al, 2012). To test this in Cicero-based links, we used our updated sci-ATAC-seq protocol to generate chromatin profiles from 662 human lymphoblastoid cells (GM12878), for which high-resolution Hi-C data was recently generated (Rao et al, 2014).…”
Section: Co-accessible Dna Elements Exhibit Physical Proximitymentioning
confidence: 99%
“…Hind III produces fragments of median length 4kb). Given that typical enhancers and promoters are considerably shorter than a single Hind III fragment (Malin et al, 2013), we hypothesised that collateral contacts may be identified along with the direct enhancerpromoter contacts they neighbour. Such collateral contacts might result from a bait traversing the regions around its primary target via Brownian motion, potentially during the formation of loops (Schwarzer et al, 2016) or from inaccuracies in the cross-linking of proximal regions during the CHi-C procedure (Belmont, 2014;Williamson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative analysis of the Hi-C data across cell lines and species reveals that while the broad 3D architecture, represented by topologically associating domains (TADs) are conserved across different cell types7, at a finer granularity, positions of chromosomal territories, compartmentalization into active and inactive regions, and specific interactions within and across TADs vary considerably. Similarly, previous studies have shown that groups of spatially clustered enhancers exhibit co-activity across cell types and this co-activity is reflected in co-expression of spatially proximal genes, which are often functionally related89. More specifically, genes involved in the same pathway have been shown to be spatially proximal in Saccharomyces cerevisiae 1011, Plasmodium falciparum 12 and Homo sapiens lymphoblastoid cell lines13.…”
mentioning
confidence: 69%
“…Previous studies have noted greater transcription in spatially clustered regions8. Independently, earlier studies have shown the existence of so called transcription factories41 - nuclear locales with enriched core transcriptional machinery components where transcripts are synthesized and processed.…”
Section: Discussionmentioning
confidence: 94%